Secure and Efficient Attribute-Based Encryption with Keyword Search. (18th April 2018) - Wang, Haijiang; Dong, Xiaolei; Cao, Zhenfu; Li, Dongmei
Abstract: Attribute-based encryption with keyword search (ABKS) is a system that supports keyword search and access control. By inheriting from attribute-based encryption technology, most current ABKS schemes incur large computation costs in encryption phase and keyword search phase. In a typical implementation, the size of ciphertext is proportional to the number of attributes associated with the access policy, so that the keyword search time and the decryption time are proportional to the number of attributes used in the access policy. To deal with the above problem, we present a new ciphertext-policy attribute-based encryption with fast keyword search scheme. Our scheme preserves the fine-grained access control inherited from the ABE system while supporting hidden policy and fast keyword search. In particular, the proposed scheme can efficiently support AND-gate access policy with multiple attribute values. Moreover, our scheme features multi-value-independent which have constant computation costs compared with the existing ABKS schemes. With the "aggregation" technique, the keyword search phase only needs three pairings, which is a great advantage over previous ABKS schemes. We offer rigorous security proof of our scheme, and the performance analysis demonstrates the efficiency of our scheme.